Dnmt3a-mediated abnormal DNA methylation is associated with myelination deficits in offspring of advanced maternal age rats - Chunxue Jiang; Xinru Yan; Man Xu; Li Cheng; Li Jiang; Wei Han (Molecular Biology Reports, 2026)

Co-occurring Spirogyra sp. and enrofloxacin stressors interact to alter macrophyte interactions: evidence from a freshwater mesocosm experiment - Yuqing Tian; Cheng Lin; Xu Zhang; Hui Yang; Hongzhi Mao; Heyin Wang; Jiali Chen; Donghai Zhang; Jiangtao Hu; Xusheng Gong; Junyan Wu; Yuying Li; et al. (Aquatic Sciences, 2026)

Comammox Nitrospira and AOB are more sensitive to warming than AOA in croplands of the North China Plain - Xiang Li; Yarui Shi; Ningning Tian; Mingmei Lu; Zhenxing Zhou; Ruixian Yang; Kesheng Zhang; Xuesong Luo; Wenli Chen; Qiaoyun Huang (Applied Soil Ecology, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

ZO-1-dependent fibrotic scar border formation impedes axon regeneration after spinal cord injury - Ziyu Li; Shuisheng Yu; Xu Wang; Xiaoyang Yu; Daobao Tao; Yongqing Ma; Jiaqi Xu; Zhonghan Wu; Zhida Ma; Dasheng Tian; Xin Ding; Meige Zheng; et al. (Science China Life Sciences, 2026)

Increased precipitation enhances microbial r/K ratios by reducing soil available nitrogen - Yuan Sun; Shangtao Jiang; Xinli Chen (Applied Soil Ecology, 2026)

Afforestation mitigates soil carbon loss in carbon-poor soils under warming - Wenwen Lv; Hailong Zhang; Yang Liao; Edith Bai; Xinli Chen; Zhenhong Hu; Jianzhao Wu; Jiwei Li; Zhouping Shangguan; Lei Deng (Applied Soil Ecology, 2026)

Synergistic organic amendments show broad potential for context-specific regulation of soil available iron in croplands - Hongyu Yu; Bingyue Yu; Erxu Xue; Chen Fu; Jing Chen; Ruiqi Yao; Pengfei Liu; Binggan Lou; Qingxu Ma; Li Chen; Kuan Xu; Jiuzhou Chen; et al. (Applied Soil Ecology, 2026)

Unravelling the role of soil enzymatic activity as a vital bioindicator of soil health and fertility in agricultural systems - Ingudam Bhupenchandra; L. Devarishi Sharma; Menaka Devi Salam; Sumit Kumar; S.K. Chongtham; Anil K. Choudhary; H. Lembisana Devi; Soibam Sinyorita; Pranab Dutta; Ali Chenari Bouket; Tatiana Minkina; Chetan Keswani (Applied Soil Ecology, 2026)

Forest nutrient context modulates microbial contributions to nitrogen acquisition during Phytolacca americana invasion - Danli Chen; Xinfu Bai; Yanhui Zhuge; Zhongjie Liu; Haokun Li; Zhaolei Qu; Xinmeng Li; Florencia Tiribelli; Yuping Hou (Applied Soil Ecology, 2026)

Cross-kingdom synthetic microbial community alleviates Cd toxicity and inhibits its uptake in rice - Xiaozhen Zhu; Qi Sun; Peiyu Li; Qingxuan Lu; Shuling Zhao; Li Chen; Shaoyuan Zhang; Hansong Chen (Applied Soil Ecology, 2026)

Plant diversity rather than soil microbial diversity drives the recovery of ecosystem multifunctionality during land restoration after rubber clearance - Qiang Lu; Xiaoqiang Lu; Xinli Chen; Xia Mao; Beibei Zhang; Jiaqi Li; Yan Liu; Xiangxiang Fu (Applied Soil Ecology, 2025)

Yak excreta increases the soil N2O emissions by regulating denitrifying bacterial diversity in the alpine marsh, Southwest China - Xuelian Guo; Wentao Li; Shanfeng Wang; Xin Fang; Li Chen; Chen Yang; Hang Wang (Applied Soil Ecology, 2025)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

Assaying the microbial features in rhizosphere of Panax quinquefolium L. under plant-derived smoke water based on metagenomic sequencing - Wanying Duan; Xiaoli Chen; Rui Li; Zhifang Ran; Lei Fang; Lanping Guo; Jie Zhou (Applied Soil Ecology, 2025)

Copper Homeostasis and Its Impact on Innate Immunity in Crustaceans - Hejia Chen; Xi Huang; Muhammad Tayyab; Mingming Zhao; Defu Yao; Zhihong Zheng; Xianliang Zhao; Yongzhen Zhao; Xiuli Chen; Bobo Zhang; Qiongqiong Yang; Yueling Zhang; et al. (Reviews in Aquaculture, 2025)
Copper, an essential micronutrient in crustaceans, plays vital roles in enzymatic processes, oxygen transport, pigmentation, and structural protein synthesis, including collagen and elastin. Recent research has elucidated its pivotal role in innate immunity of crustaceans, enhancing the immune response by promoting phagocytic activity, antimicrobial peptide production, and modulation of immune gene expression. Copper ions exhibit antimicrobial effects by disrupting cell membranes and inhibiting microbial proliferation. Furthermore, copper governs antioxidant defense mechanisms, protecting crustaceans against oxidative stress and infection. However, excessive copper can lead to toxicity, highlighting the need for strict maintenance of copper homeostasis. This review explores the complex processes of copper homeostasis in crustaceans, detailing transport mechanisms, storage proteins, and detoxification pathways. It emphasizes copper's critical physiological and immunological functions, contributing to a comprehensive understanding of its multifaceted roles in crustaceans and laying groundwork for further exploration of copper homeostasis as a strategy for boosting crustacean immunity. Aquaculture practices significantly influence copper levels in crustaceans. Effective copper management, including monitoring techniques, water treatment strategies, and regulatory frameworks, is crucial for both crustacean welfare and environmental sustainability.

Computational microfluidics of reactive transport processes with solid dissolution and self-induced multiphase flow - Chuangde Zhang; Li Chen; Xin Sha; Qinjun Kang; Zhenxue Dai; Wen-Quan Tao (Advances in Water Resources, 2024)

Impact of bacteriocins on multidrug‐resistant bacteria and their application in aquaculture disease prevention and control - Xiaoli Chen; Hong Liu; Shuangping Liu; Jian Mao (Reviews in Aquaculture, 2024)
Aquaculture plays an important role in meeting human demand for animal protein. Disease is a critical factor that restricts the green and healthy development of aquaculture. Intensive aquaculture practices can increase the susceptibility of aquatic animals to pathogens due to environmental stress. Antibiotics are commonly used for disease prevention and control, but their frequent use in aquaculture can increase the risk of antibiotic‐resistant bacteria and resistance gene transmission, posing a threat to the health of aquatic animals and humans. Recent studies have shown that bacteriocins have inhibitory effects on different species of bacteria, fungi and viruses, and can even affect natural resistance structures such as bacterial biofilms, presenting promising prospects as antimicrobial agents. Bacteriocins have potential applications in various fields such as agriculture, food and medicine, but limited research has been conducted on their impact on aquaculture disease prevention and control, and the underlying mechanisms remain to be explored. Therefore, this review aims to summarise the classification, sources, preparation methods, antibacterial activity against multidrug‐resistant bacteria and application of bacteriocins as antimicrobial agents in aquaculture disease prevention and control. In addition, limitations of bacteriocin application in aquaculture and future research directions are also discussed.

Arbuscular mycorrhizal fungi decrease soil ammonium availability and nitrous oxide emissions under nitrogen input - Xiang Zheng; Qi Liu; Xinli Chen; Minmin Cao; Fan Wu; Weiyang Li; Ling Zhang; Shenglong Liu; Jiang Jiang (Agricultural and Forest Meteorology, 2023)

A review of inclusive business models and their application in aquaculture development - Alexander M. Kaminski; Froukje Kruijssen; Steven M. Cole; Malcolm C.M. Beveridge; Claire Dawson; Chadag V. Mohan; Sharon Suri; Manjurul Karim; Oai Li Chen; Michael J. Phillips; William Downing; Fred Weirowski; et al. (Reviews in Aquaculture, 2020)
For aquaculture to continue along its current growth trajectory and contribute towards achieving the Sustainable Development Goals, value chains must become more inclusive. Smallholders and other local value chain actors are often constrained by circumstances and market failures in the global aquaculture industry. Integrating these actors into aquaculture value chains through inclusive business models (IBMs) is often touted as a solution to sustainable and ethical trade and business that can generate development outcomes. We reviewed 36 papers under seven business models commonly used in agriculture development to assess their application in aquaculture value chains in lower‐income countries. A global value chain (GVC) analysis is used to unpack the economic and social upgrading objectives of the different IBMs, as well as the types of relational coordination used between actors in the chain to achieve development outcomes. The extent to which these IBMs helped poor actors overcome certain barriers is evaluated with a focus on how they may ensure or be a risk to inclusiveness through the relations and upgrading opportunities evident in their make‐up. The analysis found that the majority of the models focused on economic upgrading over social upgrading. Providing opportunities for the latter is key to achieving the inclusive objectives of IBMs. Greater horizontal coordination between actors can create further opportunities for economic upgrading established under vertical coordination with other nodes upstream and downstream in a value chain. There is a need to further contextualize these models to aquaculture systems and develop clear indicators of inclusiveness.